2011
DOI: 10.1371/journal.pone.0019270
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Injury Evoked Loss of Latexin Expression in Spinal Cord Neurons Contributes to the Development of Neuropathic Pain

Abstract: Nerve injury leads to sensitization mechanisms in the peripheral and central nervous system which involve transcriptional and post-transcriptional modifications in sensory nerves. To assess protein regulations in the spinal cord after injury of the sciatic nerve in the Spared Nerve Injury model (SNI) we performed a proteomic analysis using 2D-difference gel electrophoresis (DIGE) technology. Among approximately 2300 protein spots separated on each gel we detected 55 significantly regulated proteins after SNI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Proteomic data from five studies show a combined 538 proteins found to be significantly modulated by the SNI model (4, 5, 28–30) (Supplementary Table S2). Of the 155 proteins found to be significantly affected by SCS therapy, 33 overlap with the 538 proteins identified in literature as affected by the injury model.…”
Section: Resultsmentioning
confidence: 99%
“…Proteomic data from five studies show a combined 538 proteins found to be significantly modulated by the SNI model (4, 5, 28–30) (Supplementary Table S2). Of the 155 proteins found to be significantly affected by SCS therapy, 33 overlap with the 538 proteins identified in literature as affected by the injury model.…”
Section: Resultsmentioning
confidence: 99%
“…Anesthesia type may not be the strongest factor for the observed differences because even though the first mouse SNI study indicates that the use of Ketamine and Xylazine precludes the development of mechanical hypersensitivity [7], several studies have used this exact cocktail and showed that mechanical hyperalgesia and allodynia develop immediately after the injury in C57BL/6 mice [12] [13]. In the acetone test for cold allodynia, the majority of papers either do not define a particular volume that is applied to the paws, or report a range of volumes, making reproducibility difficult [14]- [16]. Care must be taken in the acetone drop test because there may be a mechanical stimulation component if syringe tips touch the paws, or if the "spray" of acetone is too forceful.…”
Section: Discussionmentioning
confidence: 99%
“…With prolonged cold exposure, human motor and sensory neurons are also functionally suppressed, which leads to numbness and irreversible damages [ 3 ]. Kühlein et al [ 4 ] experimentally demonstrated that cold injury can slow cranial nerve transduction and may indirectly intensify cold injury via oxidative damage, inducing brain edema, secondary brain injury, and apoptosis. Every 1°C reduction in body temperature corresponds to a decrease in cerebral blood flow by 6%-7%, which can endanger the lives of patients sustaining traumatic brain injury.…”
Section: The Influence Of a Cold Environment On The Central Nervous Smentioning
confidence: 99%